Drafting fundamentals for the entertainment classroom : a process-based introduction integrating hand drafting, Vectorworks, and SketchUp /: a process-based introduction integrating hand drafting, Vectorworks, and SketchUp. (2021) - Appleton, Eric
No abstract available